Advanced algebra - Portman, Derek (N.Y.: Willford Press, 2019)
Algebra is one of the major branches of mathematics which studies mathematical symbols and the rules used for handling these symbols. It deals with numerous concepts such as elementary equations and abstractions such as groups, rings and fields. There are two subdomains within algebra, namely, elementary algebra and abstract algebra. Elementary algebra is the basic part of algebra and it is used in different branches of mathematics, science, engineering, medicine and economics. Advanced mathematics is a major area in abstract algebra. This book provides comprehensive insights into the field of algebra. The various advancements in this discipline are glanced at and their applications as well as ramifications are looked at in detail. The extensive content of this book provides the readers with a thorough understanding of the subject.
Upper and lower ga(B((So(BX, (So(BY)-continuous multifunctions -- On duality of modular G-Riesz bases and G-Riesz bases in Hilbert C*-modules -- Fixed point theorems for semi (Sn(B-subadmissible contractions in b-Metric -- On the convergence of the homotopy analysis method to solve the system of partial differential equations -- On weakly eR-open functions -- m-Projections involving Minkowski inverse and Range Symmetric property in Minkowski Space -- Normalized Laplacian spectrum of two new types of join graphs -- On dual shearlet frames -- Application of triangular functions for solving Vasicek model -- Lie higher derivations on B(X) -- Subcategories of topological algebras -- On the energy of non-commuting graphs -- Random fixed point theorems with an application to a random nonlinear integral equation -- Second order linear differential equations with generalized trapezoidal intuitionistic Fuzzy boundary value -- Existence and multiplicity of positive solutions for a class of semilinear elliptic system with nonlinear boundary conditions -- Probability of having nth-roots and n-centrality of two classes of groups -- On categories of merotopic, nearness, and filter algebras -- Recognition by prime graph of the almost simple group PGL(2, 25)s
Includes bibliography and index
Keywords: Algebra; Mathematical Analysis